Clinical characteristics, use and switch of drugs for obstructive airway diseases among patients with COPD experiencing an exacerbation: a retrospective analysis of Italian administrative healthcare data - Letizia Dondi; Giulia Ronconi; Silvia Calabria; Irene Dell’Anno; Leonardo Dondi; Carlo Piccinni; Ovidio Brignoli; Giorgio Walter Canonica; Mauro Carone; Fabiano Di Marco; Claudio Micheletto; Carlo Vancheri; et al. (BMC Pulmonary Medicine)
Abstract Background Chronic obstructive pulmonary disease (COPD) represents an important health challenge, despite being preventable and manageable thanks to up-to-date recommendations. In Italy, the pharmaceutical care of COPD patients is still ill-timed and inaccurate. This study aimed to describe the treatment of COPD patients in Italy and possible switches following an exacerbation. Methods This observational retrospective analysis of Italian administrative healthcare data from the Fondazione Ricerca e Salute (ReS) database identified patients aged ≥ 45 years with COPD in 2019 and 2020. At least 6 years of look-back period and absence of concomitant asthma were required. COPD patients were categorized by treatment (SI–single/MI–multiple inhalers, TT–triple therapy, DT–dual therapy, other respiratory treatments, untreated) at index date (first dispensation during accrual period). Occurrence of moderate/severe exacerbation during one-year preceding index date and treatments during one-year preceding the exacerbation (possible switch) were evaluated. Results From ~ 4.7 million beneficiaries of the Italian National Health Service in 2019 and 2020, respectively, 105,828 and 103,729 (43 and 41 × 1,000 inhabitants aged ≥ 45 years) were identified as having COPD. Of 2019/2020 patients: 3.4%/5.2% received SI-TT, 20.7%/17.5% MI-TT, 35.9%/38.1% DT, 33.0%/33.1% other treatments, and 7.0%/6.0% were untreated. Males were prevalent and median age was > 73 years for all groups. Of 2019/2020 cohorts, heart failure and coronary artery disease affected 24/20%, 18/17%, and 11%/16% patients with SI-TT, MI-TT, DT, and other treatments, respectively. A previous moderate/severe exacerbation (2019/2020 patients) occurred to 60.5%/56.6%, 39.9%/37.4%, 30.8%/29.2% and 31.9%/29.7% patients treated with SI-TT, MI-TT, DT, and other treatments, respectively. Of 2019/2020 patients experiencing moderate/severe exacerbation: 6.0%/7.0% receiving DT, 5.1%/7.0% receiving other treatments and 4.5%/10.0% untreated, switched to SI-TT; 23.7%/16.9% receiving DT, 21.4%/17.7% receiving other treatments and 15.4%/12.0% untreated, switched to MI-TT. Conclusions COPD patients receiving TT were older and had more comorbidities, especially cardiovascular diseases, than patients receiving DT or other treatments. The limited number of patients switching after exacerbation suggests that many COPD patients may be inappropriately treated. Ensuring early and adequate treatment, combination of in-hospital and outpatient management, and integration of specialist and primary care is pivotal for the appropriate clinical management of COPD patients.